The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2005
DOI: 10.1002/rcm.1811
|View full text |Cite
|
Sign up to set email alerts
|

Tandem mass spectra of transition‐metal ion adducts of glycosyl dithioacetals; distinction among stereoisomers

Abstract: Electrospray ionization mass spectra of some glycosyl dithioacetals recorded in the presence of transition-metal chlorides, XCl2 (where X = Co, Mn and Zn), give abundant adduct ions such as [M+XCl]+ and [2M-H+X]+ and minor ions such as [M-H+X]+ and [2M+XCl]+. The tandem mass spectra of these adducts show characteristic elimination of neutral molecules such as H2O, HCl, EtSH, CH2O, C2H4O2/C2H4O. [M+XCl]+ ions fragment readily and the fragmentation appears to be stereochemically controlled as the relative abunda… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2005
2005
2011
2011

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…Within the past decade, alkali, alkaline earth, and transition metal ions have been extensively used in ESI for many types of compounds. For example, metal ions have been successfully used for stereochemical differentiation by tandem mass spectrometry of some bicyclic diols [2] and glycosyl dithioacetals [3].…”
Section: Introductionmentioning
confidence: 99%
“…Within the past decade, alkali, alkaline earth, and transition metal ions have been extensively used in ESI for many types of compounds. For example, metal ions have been successfully used for stereochemical differentiation by tandem mass spectrometry of some bicyclic diols [2] and glycosyl dithioacetals [3].…”
Section: Introductionmentioning
confidence: 99%
“…Some earlier studies also showed that simple metal‐cationized monomeric or dimeric compounds exhibit stereoisomeric distinction when subjected to CID 50–53. For example, Fe 2+ ions have been used to form regioselective and stereoselective transition metal complexes and characteristic product ions by CID for structural elucidation of carbohydrates 50, 51.…”
Section: Methodsmentioning
confidence: 99%
“…Some earlier studies also showed that simple metalcationized monomeric or dimeric compounds exhibit stereoisomeric distinction when subjected to CID. [50][51][52][53] For example, Fe 2þ ions have been used to form regioselective and stereoselective transition metal complexes and characteristic product ions by CID for structural elucidation of carbohydrates. 50,51 Stereoisomeric differentiation of glycosyl dithioacetals, sulfides, sulfoxides and sulfones has also been successful using different transition-metal ion adducts and tandem mass spectrometry.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…There are a number of reviews and reports on the mass spectra of sulfur‐containing organic compounds 11–15. However, there are only a few reports on the mass spectra of S‐containing carbohydrates 16–19…”
Section: Introductionmentioning
confidence: 99%